PENGARUH ROA, INST, MAN DAN LKDT TERHADAP NP PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA Periode Tahun 2009-2011 - Sigit Riyanto, 11.42.02.0069 (Students Journal of Economic and Management, 2013)
This study is performed to examine the effect of profitability, institutional ownership, insider ownership, and liquidity toward company valueÂ  in companies that is listed in BEI over period 2009-2011. Sampling technique used here is purposive sampling on criterion (1) the company that trade their stocks in Indonesian Stock Exchange; (2) the company having insider ownership per December 2009-2011; and (3) the company that continually share their profit per December 2009-2011. The data is obtained based on Indonesian Capital Market Directory (ICMD 2012) publication. Â It is gained sample amount of 93 companies from 129 companies those are listed in BEI. The analysis technique used here is multiple regression with the least square difference and hypothesis test using t-statistic to examine partial regression coefficient and f-statistic to examine the mean of mutual effect with level of significance 5%. In addition, classical assumption is also performed including normality test, multicolinearity test, heteroscedasticity test and autocorrelation test. During 2009-2011 period show as deviation has not founded this indicate clasiccal assumption that the available data has fulfill the condition to use multi linier regression model. Empirical evidence show institutional ownership and insider ownership to have influence toward company value at level of significance less than 5%. Keywords: profitability, institutional ownership, insider ownership, liquidity and company value